2021
DOI: 10.3390/md19050270
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of Gracilariopsis lemaneiformis Polysaccharide and the Antioxidant Activity of Its Degradation Products

Abstract: Gracilariopsis lemaneiformis polysaccharides (GLP) were degraded using pectinase, glucoamylase, cellulase, xylanase, and β-dextranase into low-molecular-weight polysaccharides, namely, GPP, GGP, GCP, GXP, and GDP, respectively, and their antioxidant capacities were investigated. The degraded GLPs showed higher antioxidant activities than natural GLP, and GDP exhibited the highest antioxidant activity. After the optimization of degradation conditions through single-factor and orthogonal optimization experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…And the monosaccharide composition of IOP‐A consisted of Gal, Glc, GalA, Man, Rha, Xyl, GlcA, Fuc, and Ara. These findings were in agreement with other reports indicating that polysaccharides with lower molecular weights have excellent bioactivity (Fang et al., 2021 ; Zhao et al., 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…And the monosaccharide composition of IOP‐A consisted of Gal, Glc, GalA, Man, Rha, Xyl, GlcA, Fuc, and Ara. These findings were in agreement with other reports indicating that polysaccharides with lower molecular weights have excellent bioactivity (Fang et al., 2021 ; Zhao et al., 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…Peng et al [ 38 ] obtained the degradation products of Porphyra yezoensis polysaccharides with different molecular weights through H 2 O 2 degradation and observed the same trend when studying its oxidative stress activation on human renal epithelial cells. Fang et al [ 39 ] found that the enzymatic degradation product of the Gracilariopsis lemaneiformis polysaccharide had a better effect in alleviating oxidative damage in HFL1 cells compared to the original polysaccharide. Song et al [ 40 ] found that 600 mg/kg/bw of polysaccharides from Pleurotus geesteranus (IMPP) could significantly reduce the heightened level of MDA in the liver induced by alcohol consumption, indicating that IMPP could ameliorate alcohol-induced liver injury by alleviating oxidative stress damage in the liver, which is consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…ROS were detected through fluorescence microscopy and flow cytometry using the fluorescent probe DCFH-DA . Briefly, SH-SY5Y cells were seeded in 24-well plates, with a glass slide placed in each well (2 × 10 3 cells/well), and cultured for 12 h to allow adherence.…”
Section: Methodsmentioning
confidence: 99%